A developing world perspective on homicide and personality disorder. (July 2014) - Mela, Mansfield; Audu, Moses; Tesfaye, Markos; Gurmu, Samson
High rates of psychotic disorder among special populations of homicide offenders, females, youth and the mentally disordered, have received much investigation. Personality disorder, especially antisocial personality disorder, augments the relative risk ratio of violence, especially in combination with substance use disorder. Few studies of these correlates of violence and especially homicide have been reported in low- and medium-income countries (LMIC). Using the structured clinical interview for DSM diagnosis (SCID), personality disorders were identified in a cross sectional study involving 546 homicide offenders in Jimma prison, Ethiopia. Predictors of personality disorder were determined using multivariate analysis of various demographic and clinical variables, for example, age, psychiatric history and substance use. Out of the 316 offenders who completed the SCID, only 16% fulfilled DSM IV criteria for personality disorder. The rationale for killing, self-defence, anger and revenge (52% of offenders), planning involved in offending (50%) and reasonably high level of relationship functioning (57% married) were different from most data from the high-income countries. Diagnostically relevant cultural factors in LMIC, not in play in high-income countries, may explain the differences in personality disorders similar to other mental disorders and the underlying mediators of homicide.